Handbook of water and wastewater treatment plant operations - Spellman, Frank R. (CRC Press, 2020)
"The Handbook of Water and Wastewater Treatment Plant Operations is the first thorough resource manual developed exclusively for water and wastewater plant operators. Now regarded as an industry standard, this fourth edition has been updated throughout, and explains the material in easy-to-understand language. It also provides real-world case studies and operating scenarios, as well as problem-solving practice sets for each scenario. Features: Updates the material to reflect the developments in the field Includes new math operations with solutions, as well as over 250 new sample questions Adds updated coverage of energy conservation measures with applicable case studies Enables users to properly operate water and wastewater plants and suggests troubleshooting procedures for returning a plant to optimum operation levels Prepares operators for licensure exams A complete compilation of water science, treatment information, process control procedures, problem-solving techniques, safety and health information, and administrative and technological trends, this text serves as a resource for professionals working in water and wastewater operations and operators preparing for wastewater licensure exams. It can also be used as a supplemental textbook for undergraduate and graduate students studying environmental science, water science, and environmental engineering"-- Provided by publisher.
Keywords: Water treatment plants -- Handbooks, manuals, etc.; Sewage disposal plants -- Handbooks, manuals, etc.; Water -- Purification -- Handbooks, manuals, etc.; Sewage -- Purification -- Handbooks, manuals, etc.; elektronické knihy; electronic books